The Role of Lithium in Management of Endocrine Tumors—A Comprehensive Review - Thakur, Shilpa; Tobey, Andrew; Klubo-Gwiezdzinska, Joanna (Frontiers in Oncology, 2019)
Background Epidemiological data reveal that treatment with lithium, a mood stabilizer, is associated with decreased incidence and mortality of certain cancer types, such as melanoma. Therefore, repositioning of lithium as an anticancer agent has emerged as a promising strategy in oncology. Since lithium affects the physiology of several endocrine tissues, the goal of this study was to analyze the role of lithium in the pathogenesis and treatment of tumors of the endocrine system. Methods The databases of PubMed, EMBASE, MEDLINE, were searched from January 1970 through February 2019 for articles including the keywords “lithium and” – “thyroid cancer”, “thyroid nodule”, “parathyroid adenoma”, “parathyroid carcinoma”, “pituitary adenoma”, “pituitary neuroendocrine tumor“, “neuroendocrine tumor”, “carcinoid”, “adrenal adenoma”, “adrenal carcinoma”, “pheochromocytoma/paraganglioma”. Preclinical in vitro and in vivo studies as well as case series, retrospective cohort studies and prospective trials were selected for the analysis. Results Treatment with lithium has been associated with a higher prevalence of thyroid enlargement, hypothyroidism and increased calcium levels due to parathyroid adenoma or hyperplasia, as one of the mechanisms of its action is to stimulate proliferation of normal follicular thyroid and parathyroid cells via activation of the Wnt signaling pathway. Supratherapeutic concentrations of lithium decrease the activity of glycogen synthase kinase-3β (GSK-3β), leading to cell cycle arrest in several in vitro cancer models including medullary thyroid cancer (TC), pheochromocytoma/paraganglioma and carcinoid. Growth inhibitory effects of lithium in vivo have been documented in medullary TC xenograft mouse models. Clinically, lithium has been used as an adjuvant agent to therapy with radioactive iodine (RAI), as it increases the residence time of RAI in TC. Conclusion Patients chronically treated with lithium need to be screened for hypothyroidism, goiter, and hyperparathyroidism, as the prevalence of these endocrine abnormalities is higher in lithium-treated patients than in the general population. The growth inhibitory effects of lithium in medullary TC, pheochromocytoma/paraganglioma and carcinoid were achieved with supratherapeutic concentrations of lithium thus limiting its translational perspective. Currently available clinical data on the efficacy of lithium in the therapy of endocrine tumors in human is limited and associated with conflicting results.